2012
DOI: 10.1016/j.mrfmmm.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Niacin requirements for genomic stability

Abstract: Through its involvement in over 400 NAD(P)-dependent reactions, niacin status has the potential to influence every area of metabolism. Niacin deficiency has been linked to genomic instability largely through impaired function of the poly ADP-ribose polymerase (PARP) family of enzymes. In various models, niacin deficiency has been found to cause impaired cell cycle arrest and apoptosis, delayed DNA excision repair, accumulation of single and double strand breaks, chromosomal breakage, telomere erosion and cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 59 publications
(84 reference statements)
0
38
0
4
Order By: Relevance
“…NIC and NAM are used to modulate NAD + levels and showed therapeutic effects in disorders, such as cerebral ischemia, diabetes, and cardiovascular dysfunctions (32,33). NIC and NAM protect neurons against oxidative damage, whereas subclinical vitamin B3 deficiency is associated with genomic instability and increased cancer risk (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NIC and NAM are used to modulate NAD + levels and showed therapeutic effects in disorders, such as cerebral ischemia, diabetes, and cardiovascular dysfunctions (32,33). NIC and NAM protect neurons against oxidative damage, whereas subclinical vitamin B3 deficiency is associated with genomic instability and increased cancer risk (50).…”
Section: Discussionmentioning
confidence: 99%
“…We found that modulation of mTORC1 activity and autophagy by NAM involved SIRT1 activation in MDA-MB-453 cells, and likely depends on additional or alternative mechanisms in MDA-MB-435 and MDA-MB-231 cells. NAD + -dependent sirtuins and PARPs contribute to p53 function and regulate chromatin structure and genomic stability (32,33,50), thereby playing emerging roles in tumor progression (57). Moreover, the transcriptional corepressor CtBP responds to increased NADH under hypoxia to permit gene expression that promotes tumor cell migration (58).…”
Section: Discussionmentioning
confidence: 99%
“…Sub pellagrous NAD deficiency may be a man-made socioeconomic “place” disease that rears its head episodically as a “time” disease triggering age-related infections, degenerations, and cancers [397]. This type of socioeconomic illness does not naturally trigger an empathetic response reducing the chances of resolving the situation [398].…”
Section: Discussionmentioning
confidence: 99%
“…Na versão alcalina do teste, são detectadas lesões por quebras das fitas de DNA e sítios álcali lábeis (Singh et al, 1988 A capacidade de atuar na proteção a danos genotóxicos apresentada pela vitamina niacina já havia sido descrita anteriormente (Bartleman, Jacobs, & Kirkland, 2008;Kirkland, 2012). Em diferentes modelos experimentais, a deficiência de niacina tem sido relacionada a comprometimentos na parada do ciclo celular e apoptose, atraso no reparo do DNA por excisão, acúmulo de quebras das fitas de DNA, ruptura cromossomal, comprometimento do telômero e desenvolvimento de câncer (Kirkland, 2012). Por outro lado, a suplementação de niacina tem demonstrado proteção contra danos genotóxicos (Bartleman et al, 2008).…”
Section: Genotoxicidadeunclassified
“…O NAD+ é o substrato para as enzimas PARP que catalisam a ligação da ADP-ribose a diversas proteínas cromossômicas. As proteínas poli-ADPribosiladas funcionam na replicação e reparo do DNA, bem como em vários processos celulares incluindo diferenciação e apoptose (Kirkland, 2012 Finalmente, a presença ou não de nutrientes com ação protetora aos efeitos da exposição ao mercúrio e ao chumbo pode responder, em parte, pelo motivo das diferenças observadas nos efeitos tóxicos em populações expostas a estes metais.…”
Section: Genotoxicidadeunclassified